Kinetics of Biocatalytical Synergistic Reactions - Kulys, J. (Nonlinear Analysis: Modelling and Control, 2005)
Kinetics of biocatalytical synergistic reactions has been analyzed at non-stationary state (NSS) and at quasi steady state (QSS) conditions. The application to the model kinetic constants taken from the first type of the experiments shows that QSS can be established for the enzyme and the mediator at time less than 1 s. Therefore, the analytical solution of the initial rate (IR) may be produced at relevant to an experiment time, and the dependence of the IR on substrates concentration may be analyzed rather easy. The use of kinetic constants from the second type of reactions shows that QSS is formed for the enzyme but not for the mediator. For this reason the modeling of the synergistic process was performed by solving the ordinary differential equations (ODE). For this purpose the novel program KinFitSim (c) was used.